Marketing Strategy Preparation Case Study On CV. Gapura Creative Engineering - Pribadi, Anang; Wening , Nur (Maneggio, 2024)
This research aims to formulate an effective marketing strategy for CV. Gapura Creative Engineering through a qualitative approach. Intense competition, dynamic customer needs, and rapid technological developments require the company to formulate innovative and adaptive marketing strategies. The research methodology includes in-depth interviews with relevant parties with 5 respondents, direct observation, and document analysis to comprehensively understand the company's marketing situation. SWOT analysis was used to identify the strengths, weaknesses, opportunities, and threats facing the company. The results show that the company's main strengths lie in product quality and good reputation, while weaknesses include limitations in digital marketing and distribution. Opportunities that can be capitalized on include the growth of the digital market and strategic partnerships, while threats include intense competition and rapidly changing market trends. Based on these findings, suggested marketing strategies include increasing brand awareness through more aggressive digital campaigns, optimizing the use of social media, and developing more innovative products in line with market trends. The implementation of these strategies is expected to increase the competitiveness of CV. Gapura Creative Engineering, expand market share, and support sustainable growth. This research provides valuable insights for the preparation of a more effective and targeted marketing strategy for the company.